The Effect of Capital Structure, Liquidity, and Profitability on Firm Value - Astrieth Soputan (Malaqbi Publisher, 2026)
This study aims to examine the effect of capital structure, liquidity, and profitability on firm value. Firm value is an important indicator that reflects the market perception of a company's performance and future prospects. This research adopts a quantitative approach using secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sampling technique used in this study is purposive sampling based on specific criteria related to the availability and completeness of financial data. The data were analyzed using multiple linear regression analysis to determine the influence of capital structure, liquidity, and profitability on firm value. The results of the study show that capital structure has a positive and significant effect on firm value, indicating that companies that effectively manage their financing structure can enhance their market valuation. Liquidity also shows a positive and significant influence on firm value, suggesting that companies with strong liquidity positions are perceived as financially stable and capable of meeting short-term obligations. Furthermore, profitability has the strongest positive and significant effect on firm value, highlighting that the ability of companies to generate profits is a key factor influencing investor confidence and market valuation. Simultaneously, capital structure, liquidity, and profitability significantly influence firm value. These findings emphasize the importance of effective financial management strategies in improving company performance and increasing firm value in the capital market.